Sustainable Travel Tour: Tourism Location, Local Wisdom, Promotion and Service Quality - Prasidi, Abi (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this literature research is expected to help hypothesize for future authors in determining research related to sustainable travel tourism. Sustainable travel tourism research articles: Tourism location, local wisdom, promotion and service quality are scientific literature articles in the scope of management. The approach used in this literature review research is descriptive qualitative. Data collection techniques are using literature studies or conducting literature reviews of relevant previous articles. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Tourism Location affects Sustainable Travel Tourism; 2) Local Wisdom has an effect on Sustainable Travel Tourism; 3) Promotion affects Sustainable Travel Tourism; and 4) Service Quality affects Sustainable Travel Tourism.